Evaluation of multi drug resistance among extended spectrum β-lactamase-producing Escherichia coli causing urinary tract infection in Erbil City - Aka, Safaa Toma; Haji, Sayran Hamad (Zanco Journal of Medical Sciences (ZJMS), 2015)
Background and objective: Bacterial resistant to broad spectrum β-lactams, which is mediated by the extended spectrum beta lactamase enzyme, has emerged recently as increasing problem. Extended spectrum beta lactamase producing strains can also displaying multi-drug resistance. Thus, increased number of infections due to these strains is a public health issue associated with high morbidity, mortality, high health-care costs and prolonged hospitalization. Therefore, this study aimed to evaluate multi-drug resistance among extended spectrum beta lactamase producing E. coli causing urinary tract infections. Methods: A total of 400 mid-stream urine specimens were collected from patients with urinary tract infection. Disk diffusion agar method on Muller-Hinton agar plates was carried out. Double Disc Synergy Test was used for detection of extended spectrum beta lactamase producer. All the isolates that were screened out for extended spectrum beta lactamase production were also subjected to confirmation by using the Phenotypic Confirmatory Combination Disc Diffusion Test. Results: The urinary tract infection cases were mainly due to Gram negative bacteria (87%). E. coli was isolated from 195 (48%) specimens. Sixty isolates of E. coli (31%) were found to be extended spectrum beta lactamase producers. The resistance to antibiotics tested was significantly higher (P <0.001) among extended spectrum beta lactamase producing isolates. Conclusion: The prevalence of multi-drug resistance to the antibiotics among extended spectrum beta lactamase producing E. coli isolates was established. Imipenems are recommended for the treatment of serious infections caused by these organisms.